Sequence of hormonal therapy and radiotherapy field size in unfavourable, localised prostate cancer (NRG/RTOG 9413): long-term results of a randomised, phase 3 trial. Issue 11 (November 2018) - Roach, Mack; Moughan, Jennifer; Lawton, Colleen A F; Dicker, Adam P; Zeitzer, Kenneth L; Gore, Elizabeth M; Kwok, Young; Seider, Michael J; Hsu, I-Chow; Hartford, Alan C; Horwitz, Eric M; Yamoah, Kosj; et al.
Summary: Background: The NRG/RTOG 9413 study showed that whole pelvic radiotherapy (WPRT) plus neoadjuvant hormonal therapy (NHT) improved progression-free survival in patients with intermediate-risk or high-risk localised prostate cancer compared with prostate only radiotherapy (PORT) plus NHT, WPRT plus adjuvant hormonal therapy (AHT), and PORT plus AHT. We provide a long-term update after 10 years of follow-up of the primary endpoint (progression-free survival) and report on the late toxicities of treatment. Methods: The trial was designed as a 2 × 2 factorial study with hormonal sequencing as one stratification factor and radiation field as the other factor and tested whether NHT improved progression-free survival versus AHT, and NHT plus WPRT versus NHT plus PORT. Eligible patients had histologically confirmed, clinically localised adenocarcinoma of the prostate, an estimated risk of lymph node involvement of more than 15% and a Karnofsky performance status of more than 70, with no age limitations. Patients were randomly assigned (1:1:1:1) by permuted block randomisation to receive either NHT 2 months before and during WPRT followed by a prostate boost to 70 Gy (NHT plus WPRT group), NHT 2 months before and during PORT to 70 Gy (NHT plus PORT group), WPRT followed by 4 months of AHT (WPRT plus AHT group), or PORT followed by 4 months of AHT (PORT plus AHT group). Hormonal therapy was combined androgen suppression, consisting of goserelin acetate 3·6 mg once a month subcutaneously or leuprolide acetate 7·5 mg once a month intramuscularly, and flutamide 250 mg twice a day orally for 4 months. Randomisation was stratified by T stage, Gleason Score, and prostate-specific antigen concentration. NHT was given 2 months before radiotherapy and was continued until radiotherapy completion; AHT was given at the completion of radiotherapy for 4 months. The primary endpoint progression-free survival was analysed by intention to treat. This study is registered withClinicalTrials.gov, numberNCT00769548 . The trial has been terminated to additional follow-up collection and this is the final analysis for this trial. Findings: Between April 1, 1995, and June 1, 1999, 1322 patients were enrolled from 53 centres and randomly assigned to the four treatment groups. With a median follow-up of 8·8 years (IQR 5·07–13·84) for all patients and 14·8 years (7·18–17·4) for living patients (n=346), progression-free survival across all timepoints continued to differ significantly across the four treatment groups (p=0·002). The 10-year estimates of progression-free survival were 28·4% (95% CI 23·3–33·6) in the NHT plus WPRT group, 23·5% (18·7–28·3) in the NHT plus PORT group, 19·4% (14·9–24·0) in the WPRT plus AHT group, and 30·2% (25·0–35·4) in the PORT plus AHT group. Bladder toxicity was the most common grade 3 or worse late toxicity, affecting 18 (6%) of 316 patients in the NHT plus WPRT group, 17 (5%) of 313 in the NHT plus PORT group, 22 (7%) of 317 in the WPRT plus AHT group, and 14 (4%) of 315 in the PORT plus AHT group. Late grade 3 or worse gastrointestinal adverse events occurred in 22 (7%) of 316 patients in the NHT plus WPRT group, five (2%) of 313 in the NHT plus PORT group, ten (3%) of 317 in the WPRT plus AHT group, and seven (2%) of 315 in the PORT plus AHT group. Interpretation: In this cohort of patients with intermediate-risk and high-risk localised prostate cancer, NHT plus WPRT improved progression-free survival compared with NHT plus PORT and WPRT plus AHT at long-term follow-up albeit increased risk of grade 3 or worse intestinal toxicity. Interactions between radiotherapy and hormonal therapy suggests that WPRT should be avoided without NHT. Funding: National Cancer Institute.